Hegel’s Spectre on Indian Thought and its God-in-Nothingness - Bilimoria, Purushottama (Religions of South Asia, 2012)
This review discusses Arvind-Pal S. Mandair’s Religion and the Specter of the West: Sikhism, India, Postcoloniality, and the Politics of Translation (hereafter RSW), published in 2009 by Columbia University Press.